Biomass-Based Supercapacitors Electrodes for Electrical Energy Storage Systems Activated Using Chemical Activation Method: A Literature Review and Bibliometric Analysis - Ida Hamidah; Ramdhani Ramdhani; Apri Wiyono; Budi Mulyanti; Roer Eka Pawinanto; Lilik Hasanah; Markus Diantoro; Brian Yuliarto; Jumril Yunas; Andrivo Rusydi (Universitas Pendidikan Indonesia, 2023)
Currently, carbon derived from biomass waste or residues is being intensively utilized as electrodes due to its excellent electrical properties, including high conductivity, appropriate porosity, and a specific surface area suitable for supercapacitor applications. Despite its advantages, the performance of supercapacitors made from biomass-derived carbon is insufficient for engineering applications because of the challenges in obtaining the mesoporous structure of activated carbon (AC). Therefore, this study highlights the potential of biomass-based carbon as the electrodes of a highly efficient supercapacitor, which can facilitate highly efficient current transport in energy storage systems. It comprehensively discusses various biomass material sources and activation methods to produce carbon, with a focus on the physical and electrical properties. Initially, the study discusses carbon activation methods and mechanisms to understand why activating agents and electrolyte solutions have a high specific surface area and specific capacitance. It then concentrates on the chemical activation method and its importance in making AC useful as an efficient electrode. Finally, in this study, various biomass sources were discussed to highlight the performance of supercapacitors electrodes originating from agricultural and wood residues relating to the specific capacitance and capacitance retention. Based on the obtained results, it is concluded that biomass-based carbon materials could be the most advantageous platform material for energy conversion and storage.